Evaluation of growth, physiological response, and drought resistance of different flue-cured tobacco varieties under drought stress - Zhang, Yi-nan; Zhuang, Ye; Wang, Xiao-guo; Wang, Xiao-dong (Frontiers in Plant Science, 2024)
In recent years, more severe droughts have occurred frequently in many parts of the world, drought stress is the primary abiotic stress factor restricting the growth and quality of flue-cured tobacco. In order to reduce the negative impact, and to screenidentify suitable varieties for dryland cultivation, four flue-cured tobacco varieties were selected: Qinyan 96 (Q96), Zhongyan 101 (Z101), Yunyan 87 (Y87), and Yunyan 116 (Y116). A pot experiment was conducted with four water supply gradients: sufficient, mild stress, moderate stress, and severe stress. The aim was to analyze differences in agronomic traits, photosynthetic traits, reactive oxygen species (ROS) metabolism, and drought resistance among the varieties under drought stress.The results showed that drought intensification inhibited seedling growth and development across all varieties, with Q96 showing the least decrease and Y116 the greatest. With the increasing degree of drought stress, photosynthetic rates (Pn), transpiration rate (Tr) and stomatal conduction (Gs) have shown gradually decreasing trends, while substomatal cavity CO2 concentration (Ci) showed a growing trend.Severe drought corresponded with lower chlorophyll content and decreased the maximal photochemical efficiency (Fv/Fm), photosystem II (PSII), and photochemical quenching coefficient (qP) in all varieties, while steady-state non-photochemical quenching (NPQ) increased. Increased drought stress led to significantly higher reactive oxygen species (ROS) accumulation in tobacco seedlings. The antioxidant enzyme activities in, Q96, Z101, and Y87 increased under mild drought stress, whereas Y116 showed decreased activity. In conclusion, the drought resistance ranking among the four varieties is as follows: Q96 > Z101 > Y87 > Y116.